First report on sepsis caused by Porphyromonas pogonae. (April 2017) - Schröttner, Percy; Heidrich, Katharina; Rudolph, Wolfram W.; Stölzel, Friedrich; Jacobs, Enno; Gunzer, Florian
Abstract: We report on a 62 year old patient who developed sepsis due to an infection caused by Porphyromonas pogonae, a recently described species of the bacterial genus Porphyromonas . This is the first case of an invasive infection with this pathogen. Highlights: This is the first report on a sepsis caused by Porphyromonas pogonae . Diagnostic options to identify this just recently described species are discussed and evidence for the use of MALDI TOF MS are provided. The antimicrobial susceptibility of our strain is similar to other species of the genus Porphyromonas .